RANCANG BANGUN APLIKASI MOBILE BERBASIS UNITY SEBAGAI MEDIA EDUKASI INTERAKTIF PENGENALAN ADAT PELA GANDONG MALUKU (Studi Kasus: Negeri Rutong – Rumahkay) - Melda Dahoklory; Caryl Alyona; Eka Dharmawan; Albertus Lalaun; Calvin Berly Telapary (CV. ADIBA AISHA AMIRA, 2026)
The development method used in this study was the Multimedia Development Life Cycle (MDLC), which consists of six stages: Concept, Design, Material Collecting, Assembly, Testing, and Distribution. Data were collected through literature review, observation, interviews, and documentation. The application was developed using the Unity game engine by integrating various multimedia elements, including text, images, audio, animation, video, and interactive quizzes to enhance the user learning experience. System testing was conducted using the Black Box Testing method to ensure that all application functions operated according to the specified functional requirements. The results of the study indicate that the application was successfully developed according to the proposed design. All main features, including learning materials, the history of Pela Gandong, profiles of Rutong and Rumahkay Villages, image galleries, educational videos, interactive quizzes, background music, and navigation functions, operated properly. Based on the Black Box Testing conducted on 16 test scenarios, all application functions passed successfully, achieving a 100% success rate. Therefore, the application is considered feasible to be used as an educational medium. This study concludes that the Unity-based mobile application serves as an interactive, engaging, and user-friendly digital learning medium for introducing the history and cultural values of the Pela Gandong tradition in Maluku. The application is expected to support the preservation of local cultural heritage through multimedia technology while increasing younger generations' interest in learning about regional culture.